Haiti : the aftershocks of history - Dubois, Laurent, 1971- (New York : Picador / Metropolitan Books, 2013)
Even before the 2010 earthquake destroyed much of the country, Haiti was known as a benighted place of poverty and corruption, and has often been blamed for its own wretchedness. But as the author, a historian makes clear, its difficulties are rooted not only in its founding revolution, the only successful slave revolt in the history of the world; but also in the hostility that this rebellion generated among the colonial powers and the intense struggle within Haiti itself to define its newfound freedom and realize its promise. The author depicts the isolation and impoverishment that followed the 1804 uprising. He details how the indemnity imposed by the former French rulers initiated a devastating cycle of debt, while frequent interventions by the United States Including a twenty-year occupation, and the internal divisions and political chaos that are the inevitable consequences of centuries of subversion, further undermined Haiti's independence. At the same time, he explores Haiti's overlooked successes as its revolution created a resilient culture insistent on autonomy and equality. He also shows the internal debates about what Haiti should do with its hard won liberty that alienated the nation's leaders from the broader population, setting the stage for enduring political conflict. Yet the Haitian people have never given up on their struggle for true democracy. This book reveals what lies behind the familiar moniker of "the poorest nation in the Western Hemisphere" and illuminates the foundations on which a new Haiti might yet emerge.
Independence -- The Citadel -- Stalemate -- The sacrifice -- Looking north -- Occupation -- Second independence -- An immaterial being.
Includes bibliographical references (pages 371-413) and index.
Keywords: Haiti -- History